Now you seaweed, Now you don’t: Photographing Rongcheng’s disappearing seaweed houses - Liu, Yajing (Institutional Knowledge at Singapore Management University, 2019)
This county-level city is known not only for its picturesque beauty, but also for being the site of seaweed houses— traditional homes built from natural seaweed and stones. Inhabited mainly by local fishermen, these structures are a reflection of northern Chinese marine culture and fishery customs.